Neurotoxin localization to ectodermal gland cells uncovers an alternative mechanism of venom delivery in sea anemones - Moran, Yehu; Zenkert, Claudia; Özbek, Suat (Proceedings of the Royal Society of London. Series B, Biological sciences, 2011)
Jellyfish, hydras, corals and sea anemones (phylum Cnidaria) are known for their venomous stinging cells, nematocytes, used for prey and defence. Here we show, however, that the potent Type I neurotoxin of the sea anemone Nematostella vectensis, Nv1, is confined to ectodermal gland cells rather than nematocytes. We demonstrate massive Nv1 secretion upon encounter with a crustacean prey. Concomitant discharge of nematocysts probably pierces the prey, expediting toxin penetration. Toxin efficiency in sea water is further demonstrated by the rapid paralysis of fish or crustacean larvae upon application of recombinant Nv1 into their medium. Analysis of other anemone species reveals that in Anthopleura elegantissima, Type I neurotoxins also appear in gland cells, whereas in the common species Anemonia viridis, Type I toxins are localized to both nematocytes and ectodermal gland cells. The nematocyte-based and gland cell-based envenomation mechanisms may reflect substantial differences in the ecology and feeding habits of sea anemone species. Overall, the immunolocalization of neurotoxins to gland cells changes the common view in the literature that sea anemone neurotoxins are produced and delivered only by stinging nematocytes, and raises the possibility that this toxin-secretion mechanism is an ancestral evolutionary state of the venom delivery machinery in sea anemones.
Gesehen am 26.05.2017